Emergence of Multidrug Resistant Hypervirulent ST23 Klebsiella pneumoniae: Multidrug Resistant Plasmid Acquisition Drives Evolution - Shankar, Chaitra; Jacob, Jobin John; Vasudevan, Karthick; Biswas, Rohit; Manesh, Abi; Sethuvel, Dhiviya Prabaa Muthuirulandi; Varughese, Santosh; Biswas, Indranil; Veeraraghavan, Balaji (Frontiers in Cellular and Infection Microbiology, 2020)
Background In recent years, hypervirulent Klebsiella pneumoniae (hvKp) has been increasingly reported causing a wide range of infections with high mortality rates. In addition, frequent reports of multidrug resistant (MDR) hvKp isolates are observed. The present study characterizes two MDR hvKp isolates belonging to ST23 isolated from bacteremia using hybrid genome assembly to analyze the plasmid diversity and to gain evolutionary insights. Methods Two hvKp genomes were sequenced using Ion Torrent PGM and Oxford Nanopore MinION platforms and assembled using hybrid genome assembly for genome characterization. Results The isolates exhibited typical features of hvKp phenotypes associated with ST23 and serotype K1 and O1v2. The convergence of carbapenem-resistance (CR) and hypervirulence were attributed by the presence of multiple plasmids including a 216 kb virulence plasmid and several MDR plasmids belonging to IncA/C2, IncFIB, IncX3 and ColKp3 groups. The virulence plasmid carried aerobactin and salmochelin in addition to rmpA2 . One of the isolates was CRKp due to the presence of blaOXA-232 gene on plasmid ColKp3. The other characteristic feature is the insertion of a catA1 gene into virulence plasmid. The core genome single nucleotide polymorphism (SNP) phylogenetic analyses of the isolates showed the evolution of ST23 hvKp was predominantly driven by ICEKp. Conclusion To the best of our knowledge, this is the first report of MDR hvKp isolates of ST23 with insertion of catA1 gene into the virulence plasmid which presents the possibility of hotspot integration sites on the plasmids to aid acquiring of AMR genes. ST23 is no longer confined to susceptible strains of hvKp. Our findings emphasize the need for more studies on recombinant events, plasmid transmission dynamics and evolutionary process involving hvKp.